Adult spinal cord diffuse midline glioma, H3 K27-altered mimics symptoms of central nervous system infection: a case report - Chen, Xue; Li, Yi; Bu, Hui; Zou, YueLi; He, JunYing; Liu, Hu (Frontiers in Neurology, 2023)
Diffuse midline gliomas, H3 K27-altered are infiltrative growth gliomas with histone H3K27M mutations. This glioma is more common in the pediatric population, and the prognosis is usually poor. We report a case of diffuse midline gliomas, H3 K27-altered in an adult patient that mimicked symptoms of central nervous system infection. The patient was admitted due to double vision for 2 months and paroxysmal unconsciousness for 6 days. Initially, lumbar puncture showed persistent high intracranial pressure, high protein, and low chlorine. Magnetic resonance imaging showed diffuse thickening and enhancement of meninges and spinal meninges, and later, fever occurred. The initial diagnosis was meningitis. We suspected central nervous system infection, so we started anti-infection treatment, but the treatment was ineffective. The patient's condition gradually worsened, with lower limb weakness and even the consciousness became unclear. A repeat magnetic resonance imaging and positron emission tomography–computed tomography scan showed space-occupying lesions in the spinal cord, which was considered a tumor. Following neurosurgery, pathological tests identified the tumor as diffuse midline gliomas, H3 K27-altered. The patient was recommended for radiotherapy and temozolomide chemotherapy. The patient's condition improved after chemotherapy treatment, and he survived for an additional 6 months. Our case shows that diagnosing diffuse midline gliomas, H3 K27-altered in the central nervous system is complex and can be confused with the clinical characteristics of central nervous system infection. Therefore, clinicians should pay attention to such diseases to avoid misdiagnosis.